2009
DOI: 10.1098/rspa.2008.0410
|View full text |Cite
|
Sign up to set email alerts
|

An improved free surface capturing method based on Cartesian cut cell mesh for water-entry and -exit problems

Abstract: The free surface capturing method based on Cartesian cut cell mesh is extended to the water-entry and -exit fields with body-fluid interaction. The governing equations are the incompressible Euler equations for a variable density fluid system with a free surface, which is treated as a contact discontinuity. The solver is based on the artificial compressibility method with a dual time-stepping technique for time advancing and the finite-volume method with a high-resolution Godunov-type upwind scheme on spatial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…The contradictory results reported in Wang & Wang (2009) may indicate errors from other sources unrelated to the acceleration term in the pressure boundary condition.…”
mentioning
confidence: 44%
See 3 more Smart Citations
“…The contradictory results reported in Wang & Wang (2009) may indicate errors from other sources unrelated to the acceleration term in the pressure boundary condition.…”
mentioning
confidence: 44%
“…Further to this and as an attempt to improve the numerical stability of their code, the exact solution of a Riemann problem for moving boundaries has been used for calculating the fluxes at the boundary (Causon et al 2001). According to the authors (Wang & Wang 2009), the main reason for the inclusion of the acceleration term in the pressure boundary condition was that without this term their method would substantially under-predict the impact forces and even diverge at some point in the numerical simulation. Although it is well known that the acceleration term can be important for some flow problems where the solid boundary undergoes rapid change in velocity, it can be demonstrated that for the wedge water-entry problem as described in the experimental and theoretical work of Zhao et al 1997, this term will not have much effect on the simulation results.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus in order to better predict the force and motion of body and achieve fluid information near free surface simultaneously, a CFD method should be applied in water entry problem. Furthermore, compared with the traditional CFD method ( [36,[42][43][44] and so on), the surface capturing method [45][46][47][48] based on Cartesian cut cell mesh [47][48][49][50][51][52] as a novel method can not only well simulate complicated cases of wave breaking and trapping, but also has higher computational efficiency to treat moving boundaries by updating a few cut cells locally rather than remeshing the whole flow domain. On the other hand, so far there are only few documents which consider the interaction among fluid field, global motion, and local deformation of elastic body simultaneously for the water entry problem.…”
Section: Introductionmentioning
confidence: 99%